Effects of plant location on cost of CO2 capture. (November 2019) - Ferrari, Noemi; Mancuso, Luca; Burnard, Keith; Consonni, Federico
Highlights: CCS in SC-PC and NGCC plants considered across 13 different countries. Different design parameters affect plant efficiency up to of 3% points. LCOE in coal plants with CCS varies in the 68-106 €/MWh range, main variations driven by coal price, labour costs and materials costs. LCOE in NGCC plants with CCS varies in the 48-93 €/MWh range, main variations driven by cheap natural gas availability. CCS leads to an increase in LCOE of +80-100% for SC-PC plants and +40-70% for NGCC plants. Cost of CO2 avoided varies in the 48-74 €/tCO2 range for SC-PC plants and 62-95 €/tCO2 for NGCC plants. Abstract: Most economic assessments addressing the application of CO2 Capture and Storage (CCS) applications to fossil fuel fired power plants reported in literature are either focused on a specific country or consider a hypothetical site in the U.S. or The Netherlands. Although these may be regions where large-scale power plants with CCS will be built, there is greater potential for CCS in regions where coal consumption is greater and expected to increase or where emission reduction targets would imply CCS to be considered also in gas fired power stations. The main objective of this paper is to investigate and quantify how the costs of CO2 capture are likely to vary for different locations, summarizing the results of a dedicated IEAGHG study developed by Amec Foster Wheeler Italiana. The paper focuses on supercritical pulverised coal (SC PC) and natural gas combined cycle (NGCC) power plants. Post combustion capture based on solvent scrubbing only has been considered, being currently the commercially leading option for capture. Variations in the performance and costs of plants have been quantified, according to local and site-specific conditions. The main parameters that have been identified as affecting plant performance and costs are technical differences between the sites (mainly ambient conditions and fuel analysis) and economic parameters (mainly fuel price, labour costs and productivity and local costs of material).